2010
DOI: 10.1128/jcm.01420-09
|View full text |Cite|
|
Sign up to set email alerts
|

First Report Worldwide of an Infant Botulism Case Due to Clostridium botulinum Type E

Abstract: Clostridium botulinum type E has been associated with botulism in adults but never in infants. Infant botulism type E cases have been associated with neurotoxigenic strains of C. butyricum . We report the first infant botulism case due to C. botulinum type E worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…For example, the vast majority of colonization botulism cases are a result of group I C. botulinum, C. baratii, and C. butyricum strains, presumably because they prefer a higher incubation temperature to group II C. botulinum strains [29]. Yet, recently a case of infant colonization botulism was reported as caused by a group II C. botulinum, type E, which have an optimal growth temperature of 25 • C [81]. Considering that adult intestinal toxemia botulism is difficult to diagnose and exceptionally rare, a concerted effort by healthcare professionals should be taken to identify and characterize this form of botulism.…”
Section: Recognition Of Casesmentioning
confidence: 99%
“…For example, the vast majority of colonization botulism cases are a result of group I C. botulinum, C. baratii, and C. butyricum strains, presumably because they prefer a higher incubation temperature to group II C. botulinum strains [29]. Yet, recently a case of infant colonization botulism was reported as caused by a group II C. botulinum, type E, which have an optimal growth temperature of 25 • C [81]. Considering that adult intestinal toxemia botulism is difficult to diagnose and exceptionally rare, a concerted effort by healthcare professionals should be taken to identify and characterize this form of botulism.…”
Section: Recognition Of Casesmentioning
confidence: 99%
“…A recent outbreak of botulism in birds and fish in the Great Lakes region was attributed to genetically distinct strains of C. botulinum type E and the organism was also found in lake sediment [6]. A case of infant botulism occurred in Illinois in 2007 although the source of spores in this case could not be determined [7]. …”
Section: Introductionmentioning
confidence: 99%
“…BabyBIG } is available for treatment of infant botulism type A and type B, and the titers of antibodies in BabyBIG } against type A and B botulinum toxin are at least 3,000 and 540 LD 50 /mg antibody, respectively. Although the level of antibody against type E has not been measured, L áuquez et al reported that a patient rapidly recovered from type E infant botulism owing to treatment with BabyBIG } (27). We suggest that EC94 possesses high neutralizing activity against type E comparable to that of BabyBIG } , given estimates from the antibody titers against types A and B.…”
Section: Resultsmentioning
confidence: 99%